Pendampingan Pembuatan Pupuk Organik Cair dari Limbah Ikan Hasil Tangkapan Sampingan Udang di Desa Tanjung Pademawu - Silawati, Anis; Putri, Intan Dian Kusumaning; Chandra, Adyos Bobby; Pratiwi, Wiwit Sri Wedi; Alfisuma, Meria Zakiyah; Hafiludin, Hafiludin (Jurnal Ilmiah Pangabdhi, 2024)
Tanjung Village is a village with quite high fisheries potential, one of them is the potential of shrimp. This potential provides fishery waste in the form of by-catch. The aim of this service is. to provide outreach, understanding and training to the community about making liquid organic fertilizer from fish waste from shrimp by-catch. The method for implementing this service is identification, socialization and training. The search results obtained types of fish from shrimp by-catch, namely juvenile demersal fish and other biota that were caught. Socialization activities were carried out by providing education which was attended by the Tanjung village community. The training activity is providing education regarding how to make liquid organic fertilizer from shrimp by-catch fish. The results of this activity will have an impact on the economic activities of the Tanjung community in the future.